COVID-19 Infection in Adrenal Tuberculosis Patients with Adrenal Insufficiency Who Complicated with Adrenal Crisis - Matdoan Rifkiah Aisyah; Ira Camelia Fitri; Ardhi Rahman Ahani; Syahidatul Wafa (Interna Publishing, 2024)
Adrenal insufficiency can increase the risk of infection. Respiratory infections play a role in the greater number of mortalities in patients with primary adrenal insufficiency. Severe acute illness elevates the risk of adrenal crisis which can give lethal outcome. A 52-year-old woman came to the emergency unit due to worsening gastrointestinal symptoms for the past 3 days. She had chronic epigastric pain, general weakness, weight loss, and skin hyperpigmentation. She was suspected of primary adrenal insufficiency one year ago, but she had poor compliance. In this current admission, she was suspected to have adrenal crisis and was diagnosed with COVID-19. On the 5th day of inpatient care, her condition was worsening, and she was diagnosed with adrenal crisis, septic shock, and severe COVID-19. Her ACTH level was 78.6 pg/mL (normal range 7.4-64.3 pg/mL) and her morning cortisol level was 1.1 ug/dL (normal range 3.7-19.4). Imaging showed unilateral hypertrophy of the adrenal gland, a positive result of IGRA, and fibrotic of the lung that led to tuberculosis of the adrenal as suspected etiology. Making a diagnosis of adrenal insufficiency is challenging because of its non-specific signs and symptoms. The need for education, equipment (adequate steroid supplies), and empowerment (development of specific guidelines for PAI and COVID-19) were taught to help prevent the adrenal crisis. Further examination is needed to obtain the definitive etiology of adrenal insufficiency in this patient.